Pitch Lake, Trinidad, B.W.I. - (:unkn) unknown (Stephens Ltd., Trinidad, 2010)
Photo of blue collar workers at the Pitch Lake in Trinidad digging for pitch by a railroad/railway. Postcard number 12 50068.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Pitch; Asphalt industry--Trinidad and Tobago; Railroads--Trinidad and Tobago; Blue collar workers--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--La Brea; Forests and forestry--Trinidad and Tobago; [1910]; Employees--Trinidad and Tobago; Work; Working class--Trinidad and Tobago; Men--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Hats--Trinidad and Tobago; Transportation--Trinidad and Tobago; Employees--Trinidad and Tobago; Axes--Trinidad and Tobago; Tools--Trinidad and Tobago; Manual work--Trinidad and Tobago; Trees--Trinidad and Tobago; Pitch Lake, The (La Brea)